2009
DOI: 10.1016/j.jaci.2009.02.026
|View full text |Cite
|
Sign up to set email alerts
|

IL-33–activated dendritic cells induce an atypical TH2-type response

Abstract: Background-IL-33, a recently discovered IL-1 family cytokine, is implicated in the development of Th2-type responses in vivo. However, the cellular target(s) for IL-33 are poorly understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
267
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 354 publications
(280 citation statements)
references
References 49 publications
11
267
1
1
Order By: Relevance
“…36 IL-33-activated DCs induce what has been described as an atypical Th2-type response characterized by IL-5 and IL-13, with no IL-4. 37 The addition of recombinant IL-33 to cultured asthmatic DCs in the present study dose dependently induced chemokine ligands 17 and 22, but not IL-12p70, generation by these cells (H.R. and C.M.H., unpublished data).…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…36 IL-33-activated DCs induce what has been described as an atypical Th2-type response characterized by IL-5 and IL-13, with no IL-4. 37 The addition of recombinant IL-33 to cultured asthmatic DCs in the present study dose dependently induced chemokine ligands 17 and 22, but not IL-12p70, generation by these cells (H.R. and C.M.H., unpublished data).…”
Section: Discussionmentioning
confidence: 51%
“…allergic asthma, 43 including attenuation of asthmatic responses driven by both fungus 37 and fungal proteases. 54 The role of MIG/CXCL9 in asthma is less clear, but this CXC chemokine is strongly induced by IL-12.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myeloid DCs generated in the presence of IL-33 exhibit a relatively limited T-cell stimulatory capacity compared with conventional DC cultures established with GM-CSF. On the other hand, Rank et al reported that mature DC treatment with IL-33 upregulated cell-surface expression of MHC class II molecules and the costimulatory molecule CD86 [29]. Furthermore, IL-33-activated DCs could polarize CD4 1 T cells to produce IL-5 and IL-13, suggesting that IL-33 may play a role in the induction of adaptive immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…The cytokine expression pattern of T cells polarized by IL-33-activated DCs differs from classical Th2 cells by the absence of IL-4 production. An atypical Th2 subset upon IL-33 activation has been reported, which is independent of IL-4, GATA3 and TCR engagement [26,29].The contribution of IL-33 on asthma symptoms by its direct action on mast cells, basophils, eosinophils and Th2 cells has been Figure 7. IL-33 enhances allergic airway inflammation induced by OVA-pulsed DCs.…”
mentioning
confidence: 99%